Pengaruh Penambahan Tepung Talas Kimpul (Xanthosoma Sagittifolium) Pada Pembuatan Bolu Kukus Terhadap Tingkat Pengembangan Dan Daya Terima - Inayah, Rafika Nurul, Eni Purwani, S.Si., M.Si, Dwi Sarbini, S.ST., M.Kes (2017)
Steamed cake is a cake made from flour and cooked by steamed. Steamed cake has a pretty good prospect because almost all of age like it. The use of wheat flour in Indonesia as a raw material for the manufacture of food products tend to experience increased every year. This trend will directly impact national food thickness. Therefore, it is necessary to other materials that can be processed to be able to subtitute the use of flour in Indonesia. One of them is the use of talas kimpul flour as material substitution for wheat flour. to know the influence of the addition of talas kimpul (Xanthosoma sagittifolium) flour in level of development and acceptibility oin making of steamed cake. Experimental research designs with complete random design (RAL) using 3 treatments and 1 control with 3 repetitions. comparison flour taro kimpul are 0%, 12.5%, 25% and 37.5%. Measurement of the level of development of the steamed cake done by measuring at 3 points. Test the power received steamed cake made against 30 panelists. Statistical tests the level of development of the steamed cake with Annova and received with the Kruskal Wallis test and continued with Duncan. the rate of development of the optimal treatment of refractory steamed cake with talas kimpul flour 12.5%. The level of fondness steame cake preferred panelist is steamed cake with the addition of talas kimpul flour 12.5%. There is the influence of the addition of talas kimpul (Xanthosoma sagittifolium) flour in level of development and acceptibility in making of steamed cake.